Pengaruh Fenomena La Nina terhadap Produktivitas Tanaman Kopi di Afdeling Rayap Kabupaten Jember - Rina Kumalasari (Fakultas Pertanian, 2026)
This research aims to determine the comprehensive influence of the La Niña phenomenon on coffee productivity, specifically focusing on the Renteng Banjarsari Plantation located in Jember. This intensive study was conducted at Afdeling Rayap from September to December 2025 to capture a clear picture of how climate anomalies affect agricultural output. This study addresses the urgency of SDGs 13 (Climate Action) as a concrete effort to provide empirical data for developing adaptation strategies in the plantation sector against extreme weather. This research utilizes a combination of correlation and regression methods to analyze the extent to which global phenomena, such as La Niña, impact coffee productivity based on empirical data, including long-term productivity records and historical rainfall data from the Afdeling Rayap station. Geographically, Afdeling Rayap is situated in Jember Regency, East Java, at an optimal altitude of 550 meters above sea level for coffee cultivation. Secondary data obtained from the plantation administration were meticulously analyzed using percentile determination and logistic regression calculations. The research sample utilized a 15-year observation period from 2011 to 2025 to ensure data reliability. The final calculation employed a logistic regression model to measure the precise magnitude of the La Niña phenomenon's effect on the fluctuations of coffee productivity over the decade. The recorded La Niña events and normal years during this 15-year period were 2012, 2013, 2014, 2017, 2018, and 2025, which were categorized as normal years, and 2011, 2020, 2021, and 2022, which were categorized as Weak La Niña. Based on the percentile value calculations, the rainfall during normal years was 4,210 and surged to 7,263 during La Niña years. This value aligns with the decline in coffee productivity, where the productivity percentile during normal years was 398 but plummeted to 191 during La Niña years. Meanwhile, the results of the logistic regression analysis indicate that Sea Surface Temperature (SST) has a 21.4% influence on the decline of coffee productivity and a 14% influence on rainfall changes at Afdeling Rayap. These findings reinforce the importance of local climate action (SDGs 13) to mitigate the risk of crop yield decline. Apart from climate factors, the decline in productivity at Afdeling Rayap is also influenced by the biological traits of the coffee plants, such as biennial bearing, an innate cycle where coffee trees experience alternating heavy-fruiting phases (on-year) and low- yielding phases.
FINALISASI oleh Arif 2026 Juni 18
Keywords: Fenomena La Nina; Curah Hujan; Produktivitas Kopi